Transforming Islamic Education for Environmental and Social Sustainability - Hajar, Andi (Yayasan Sinergi Kawula Muda, 2024)
This study explores the contributions of Islamic education to sustainable development by reviewing recent literature on curriculum innovation, environmental awareness, institutional engagement, and technological adaptation. The aim is to assess how Islamic educational institutions integrate sustainability principles through religious values and pedagogical strategies. Using a narrative review approach, literature from Scopus and Google Scholar was analyzed based on keywords such as